Suicide attempts in schizophrenia patients: a retrospective study - Ish Garg; Bobby Hmar; Priyam Sharma; Shyamanta Das (Open Journal of Psychiatry and Allied Sciences)
Objectives: Schizophrenia is a major and disabling chronic mental illness with variable course. The presence of suicide death and suicide attempts causing more severity of the psychopathology of these populations with schizophrenia. Both sexes are affected and the presence of substance abuse increases the vulnerability to suicide in these populations. So, aim of the study is to estimate the prevalence of suicide attempts and its related clinical variables in patients diagnosed with schizophrenia. Methodology: This is a retrospective study. Data was collected between January 2018 and December 2018 from the patients’ case history sheet. The clinical data proforma was prepared for data collection. ICD-10 diagnostic criteria had been used to diagnose patients with schizophrenia. Both male and female patients between 18 to 60 years had been enrolled in the study after fulfilling the selection criteria. Descriptive statistics had been applied in this study. Results: A total of 234 patients’ data were collected and 54.3% were male followed by 45.7% were female. The prevalence of suicide attempts was estimated at 4.34%. The mean age of suicide attempter was 27.3 years. Out of 234 patients, a family history of suicide was 6.9%, a family history of schizophrenia was 17.8% followed by a family history of substance abuse in 46.5% was recorded. Conclusion: The percentage of suicide attempter in diagnosed cases of schizophrenia has been found to be lower (4.34%) in this region of the globe in comparison to other parts of the world. The risk factors for suicide attempters in this study are male gender, young adult, and presence of substance abuse.